The impact of emotional intelligence and cultural intelligence on job performance in Russia - Engle, Robert; Dimitriadi, Nikolay; Toskin, Katarzyna (Journal of Management Policy and Practice, 2026)
A great deal of work has been done in recent decades examining the impact of emotional intelligence (EQ) and cultural intelligence (CQ) on extra-role job performance. However, little of this research has used both EQ and CQ constructs together in the same analytical model. In addition, the available literature in is virtually silent with regards to the relationships of these constructs in Russia, a country with a significant multicultural environment. This study examines these relationships, using a sample of 189 supervisory and non-supervisory subjects in Russia. The results suggest that motivational CQ may be seen as an antecedent of CQ and EQ, both of which significantly impact extra-role job performance. EQ and CQ factors were also found to mediate the relationship between motivational CQ and extra-role job performance. In addition, necessary condition analysis was completed adding to model insights. These results extend our knowledge to a Russian sample, and not only support the Thomas et al. (2015) approach to CQ, but also suggest significant implications for current EQ-CQ model theories.
Keywords: Antecedent (behavioral psychology); Cultural intelligence; Emotional intelligence; Job performance; Multiculturalism; Sample (material); dept.bis